Patterns of Metacognitive Skills and External Representation of Students in Chemistry Problem Solving - Ijirana, Ijirana; Mansyur, Jusman (Universitas Negeri Malang, 2019)
This research aims to examine the pattern of external representation and metacognitive skills in chemistry problem solving for students of chemistry education at Tadulako University. This picture will enrich the treasures of thinking skills in the field of science, namely how students/prospective teachers think in the context of metacognitive skills and how these students display an external representation system on chemistry concepts. The subject of this qualitative study was obtained through a purposive random sampling of 97 students who have been programmed Basic Chemistry course 2017/2018 academic year. Subjects were selected based on the results of the screening using a metacognitive skills assessment questionnaire (MCAI). Two problems solved by the subject by setting one-on-one thinking aloud. Subjects who complete the issue by setting further interviews at different times. The problem-solving activity was recorded using a video camera. The subject uses a type of representation and aspects of metacognitive skills and how to use the sequence of activities, analyzed in detail. The results showed that students of chemical education used metacognitive skills and external representations. So students solve chemical problems. Students also can improve knowledge retention related to linking new knowledge with previous knowledge, creating ideas, organizing, and even synthesizing knowledge. Students become productive and find solutions for problem-solving well